Local public goods, adaptive migration decisions and agglomerative bias - Andreas Kopp (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1999)
In this paper we examine how uncertainty might lead to an agglomerative bias in the domain of competition between jurisdictions for mobile citizens. Since Tiebout's (1956) seminal work asserting that competition between jurisdictions would lead to a first best allocation even in the presence of public goods much of the research has addressed normative questions. The models employed differ with respect to what extent and in which way the public good is congestible, making it a local public good, with respect to incorporating a land market, with respect to the possible entry of new communities, the mobility of the consumers and the ability of the communities' authorities to control the residence in their communities. From a first best perspective only the consequences of population (congestion) entering consumers' utility functions and the population (congestion) entering the production function are of analytical interest. All the other features taken as given in other models of local public finance should be at the discretion of the social planner (Berliant 1998).
Keywords: 330; Lokales öffentliches Gut; Agglomerationseffekt; Abwanderung und Widerspruch; Anpassung; Theorie; Entscheidung bei Unsicherheit